James Couzens papers - Couzens, James, 1872-1936.
Correspondence, articles, speeches, subject files, scrapbooks, and other papers relating to Couzen's work with the Ford Motor Company (1903-1915), campaign for mayor of Detroit in 1918, service in the U.S. Senate (1922-1936), and farm near Pontiac, Mich. Correspondents include James Francis Byrnes, Arthur Capper, John J. Carson, Roy D. Chapin, Charles E. Coughlin, Glenn Hammond Curtiss, Joseph Edward Davies, Horace E. Dodge, John F. Dodge, Henry Ford, William Green, Edgar A. Guest, Herbert Hoover, Cordell Hull, Jesse H. Jones, Charles Horace Mayo, Frank Murphy, Herbert Bayard Swope, Arthur H. Vandenberg, and William H. Woodin.
Library of Congress Prints and Photographs Division.
U.S. senator from Michigan, mayor of Detroit, Michigan, and industrialist.
Collection material in English.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Keywords: Byrnes, James F. -- 1882-1972 -- Correspondence; Capper, Arthur, -- 1865-1951 -- Correspondence; Carson, John J. -- 1889- -- Correspondence; Chapin, Roy D. -- 1880-1936 -- Correspondence; Coughlin, Charles E. -- 1891-1979 -- Correspondence; Curtiss, Glenn Hammond, -- 1878-1930 -- Correspondence; Davies, Joseph Edward -- Correspondence; Dodge, Horace E. -- 1868-1920 -- Correspondence; Dodge, John F. -- 1864-1920 -- Correspondence; Ford, Henry, -- 1863-1947 -- Correspondence; Green, William, -- 1870-1952 -- Correspondence; Guest, Edgar A. -- 1881-1959 -- Correspondence; Hoover, Herbert, -- 1874-1964 -- Correspondence; Hull, Cordell, -- 1871-1955 -- Correspondence; Jones, Jesse H. -- 1874-1956 -- Correspondence; Mayo, Charles Horace, -- 1865-1939 -- Correspondence; Murphy, Frank, -- 1890-1949 -- Correspondence; Swope, Herbert Bayard, -- 1882-1958 -- Correspondence; Vandenberg, Arthur H. -- 1884-1951 -- Correspondence; Woodin, William H. -- 1868-1934 -- Correspondence; United States. -- Congress. -- Senate; Ford Motor Company; Agriculture -- Michigan -- Pontiac; Automobile industry and trade -- United States; Farms -- Michigan -- Pontiac; Detroit (Mich.) -- Politics and government; Michigan -- Politics and government; United States -- Politics and government -- 1901-1953.; Industrialists; Mayors -- Michigan -- Detroit; Senators, U.S. Congress -- Michigan